Highly-selective recognition of latent fingermarks by La-sensitized Ce nanocomposites via electrostatic binding. Issue 71 (16th August 2019) - Peng, Di; Huang, Mengjun; Xiao, Yaruo; Zhang, Yuyan; Lei, Li; Zhu, Jiang
Abstract : A series of binuclear (Ce, La) nanocomposite fluorescent powders was elaborately designed for highly-selective recognition of latent fingermarks, which were proved to combine with fingermark residues electrostatically without any damage to touch-DNA. Abstract : Herein, a series of binuclear (Ce, La) nanocomposite fluorescent powders was elaborately designed for highly-selective recognition of latent fingermarks by the powder dusting method, which were proved to interact with fingermark residues via electrostatic binding without any damage to touch-DNA.